Training of Implementation of Simple Financial Statements on Waste Bank Group in West Jakarta - Helsinawati Helsinawati (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2017)
Regulation of the Minister of Environment No 13 of 2012 on the implementation of Reduce, Reuse, and Recycle (Ministry of Environment, 2012) is to manage waste through 3R principles (Reduce, Reuse, and Recycle). This regulation drives the community to establish a waste bank. Community Service on Training on Implementation Simple financial report on waste bank group aims to; provide theory, demonstration and practice about account code creation, document formats, and financial transaction processing on Member Savings Books / Waste customers. A waste bank is a concept of collecting and sorting dry waste, and has management like a bank but a savings is not of money but rubbish. Waste bank report, Purchase Report, Debt Report, Sales Report, Receivable Report and Cash and Cash Equivalent Report, Inventory Report, Journal, General Ledger, Trial Balance and Financial Statement (Balance Sheet, Income Statement and Cash Flow) Waste bank can monitor and control the source and the use of funds . The efficiency and accountability of revenue and expenditure of funds can be better so that profitability of business can increase. Training methods used (1) Lecture and Discussion, (2) Demonstration, and (3) Direct Practical Simple Finanvial Statement . Outcomes of this activity are the Improvement of knowledge, better understanding, skills of application of financial report recording from Waste Bank management.